International Conflict and its Implications for Nepal’s Development/Prosperity - Kharel, Hemanta (NCWA Annual Journal, 2025)
Since the beginning of human civilization conflict remains an inseparable part of human society. In today’s world conflict is an expression of heterogeneity of interest combined with amalgamation of values and belief. The most challenging job of the contemporary state is the resolution of conflicts and uniting the major layers of society around itself so as to lead the people towards development and prosperity. It is commonly believed that least developed countries are negatively affected by conflicts both in short term and long term economic and social outcomes compared to developing and developed countries. Directly and indirectly the implications of international conflict in Nepal cannot be underestimated. Nepal needs to make every ef fort for better and efficient use of foreign assistance to minimize the implications of conflicts and also should commitments for efficient governance, rule of law, transparency and accountability, zero tolerance of corruption as well as fair and equal distribution of resources.